Thermoviscoelastic Modeling of Thermoplastic Polymers - Keursten, Johannes (KIT Scientific Publishing, 2025)
This work presents the theory of linear thermoviscoelasticity. Mechanical and calorical part of the model are formulated by using an analogy. The corresponding parts of the model are applied regarding two specific problems. First, the modeling of the viscoelastic behavior of polyamide 6 under hydrothermal influences is considered. In addition, the process-dependent calorical behavior of polystyrene in the vicinity of the glass transition is modeled.